In vitro evaluation of 14 culture media on the mycelial growth of Moniliophthora perniciosa (Stahel) Aime & Phillips-Mora - Huaman Pampañaupa, Jhojan Sven (2021)
Cocoa cultivation in Peru is increasing due to the expansion of productive areas and improved yields, however, the presence of the three main diseases (brown ear, witch's broom and moniliasis) significantly affect the yields in cocoa plantations with low maintenance level, with the objective of determining the culture media that allow greater radial growth of Moniliophthora perniciosa, for which it is necessary to have viable management and control strategies. In vitro tests of chemical and biological control require that the isolates present appropriate mycelial growths, for which reason the comparison of 14 non-conventional solid culture media with 6 repetitions was proposed. The treatments were maltacervezneg, caraota bean, achiote, cascmazorca, rice, yellow corn, frugos, mbamilaceo, potato, molazacacao, vegetables, masabourd, broom green and gelatin, on which basidiocarps of M. perniciosa from Cacaopampa-Santa Ana were planted, glued in the center of the lid of the 90 mm petri dishes and incubated for 12 days at 25 ° C temperature. The culture media that allowed greater radial growth of M. perniciosa were medium malt from dark beer, caraota beans, achiote and cocoa husk with 90.00, 87.08, 82.58 and 66.75 mm respectively and the medium potato (PDA) presented a performance of 50 % lower than the Maltacerveneg medium in the radial growth of monosporic culture of M. perniciosa.